The Dynamics of the Aceh Special Local Elections Following the Constitutional Court Ruling - Ridwansyah, Muhammad; Zakyyah, Zakyyah; Abidin, Zainal (Journal of Dual Legal Systems, 2025)
The Constitutional Court Decision No. 135/PUU-XXII/2024 provides new hope for reformulating the separation of local elections in Aceh. Article 65 of UUPA provides legal standing that local elections specifically for Aceh are held directly by the people every 5 (five) years through democratic, free, secret elections and are carried out honestly and fairly. The issue of separating local elections in Aceh since 2022 should still refer to the formulation of the norms of a quo article, but it was ignored by the Indonesian Government because according to the norms of Article 201 of Law No. 10 of 2016, it annuls the special status of local elections in Aceh, thus local elections in Aceh will still be held in 2024. The formulation of the problem includes: How is the relevance of the norming of Article 65 of Law No. 11 of 2006 related to Constitutional Court Decision No. 145/PUU-XXII/2024? How should local elections specifically for Aceh be after the Constitutional Court Decision MK a quo? The analysis method used is normative legal research with three approaches, namely the statutory approach, the conceptual approach, and the analytical approach. Result: That the relevance of the normativeization of Article 65 of Law No. 11 of 2006 finds a meeting point which has been considered a debate that local elections are directed to become an election regime, not a regional government regime as mandated by Article 18B paragraph (4) of the 1945 NRI Constitution. Then, that the local elections specifically for Aceh are in accordance with Article 18B a quo Constitution and become a norm for special elections because the special nature of elections in Aceh can override general election norms so that the authority of Article 18B paragraph (4) of the 1945 NRI Constitution and Article 65 of UUPA is upheld. [ Putusan MK No. 135/PUU-XXII/2024 memberikan harapan baru untuk merumuskan kembali pemisahan pilkada lokal di Aceh. Pasal 65 UU No. 11 Tahun 2006 memberikan legal standing bahwa pilkada lokal khusus Aceh secara langsung oleh rakyat setiap 5 (lima) tahun sekali melalui pemilihan yang demokratis, bebas, rahasia serta dilaksanakan secara jujur dan adil. Seharusnya isu pemisahan pilkada lokal di Aceh sejak tahun 2022 tetap mengacu pada rumusan norma pasal a quo, namun tidak digubris oleh Pemerintah Indonesia karena menurut norma Pasal 201 UU No. 10 Tahun 2016 menganulir kekhususan pilkada lokal Aceh, dengan demikian pilkada lokal Aceh tetap dilaksanakan pada tahun 2024. Perumusan masalah antara lain: Pertama, bagaimana relevansi penormaan Pasal 65 UU No. 11 Tahun 2006 terkait Putusan MK No. 145/PUU-XXII/2024? Kedua, bagaimana seharusnya pilkada lokal khusus Aceh pasca Putusan MK MK No. 135/PUU-XXII/2024? Metode analisis yang digunakan penelitian hukum normatif dengan tiga pendekatan yakni pendekatan perundang-undangan, pendekatan konseptual, dan pendekatan analisis. Kesimpulan: Bahwa relevansi penormaan Pasal 65 UU No. 11 Tahun 2006 menemukan titik temu yang selama ini dianggap menjadi perdebatan bahwa pilkada lokal diarahkan menjadi rezim pemilu bukan menjadi rezim pemda seperti yang diamanahkan oleh Pasal 18B ayat (4) UUD NRI 1945. Kemudian, bahwa pilkada lokal khusus Aceh sudah sesuai dengan Pasal 18B ayat (4) UUD NRI Tahun 1945 dan menjadi norma kekhususan pemilu karena kekhususan pemilu di Aceh dapat mengeyampingkan norma pemilu umum sehingga otoritas Pasal 18B ayat (4) UUD NRI Tahun 1945 dan Pasal 65 UU No. 11 Tahun 2006 ditegakkan.]